Achieving environmental sustainability in Malaysian construction industry through institutional pressure - Ajibike, W. A.; Adeleke, A. Q.; Fazeeda, Mohamad; M. N. M., Nawi; Bamgbaded, J. A.; S. R. M., Riazi; Md Fauzi, Ahmad (Advance Scientific Research, 2020)
Construction firms around the world are under pressure to minimize consumption of resource, avoid destruction of natural environment, prioritize clients’ call for environmentally responsiveprojects, and be upbeat in dealingwith their firm developmentso as to preserve both the natural and built environment.Construction firms that comply with institutional requirements regarding environmental care are well-positioned to recognize the modifications in their clients’ choices regarding environmental sustainability and therefore, take a swiftaction towards fulfilling the environmental sustainability agenda. The aim of this study is to conceptualize the effect of institutional pressure on environmental sustainability adoption by construction firms in Malaysia using institutional theory to reinforce these relationships. The extant literature has highlighted environmental sustainability as one of the most important interests of most 21st century firms because their compliance with institutional regulations and the ecological environment that supports all life are intimately connected. Although it is anticipated that the outcomes of this review could be used to create policies that could improve environmental sustainability adoption among these firms, this study did not take into consideration other factors that may also explain the environmental sustainability adoption. It is expected that this study’s findings could assist in developing policies to boost the rate of environmental sustainability implementation among firms. Again, it could also be useful for policy makers and other players in theconstruction sector.